Pembuatan E-Commerce untuk “Lugz Shoes Collezione” - Marshall Sudharmono; Djoni Haryadi Setiabudi; Indro Setiawan (Jurnal Infra, 2017)
LUGZ Shoes Collezione is a store that sells products such as shoes as the main product and stand in Malang since July 23, 2005. To resolve an issue which a customer is not able to use some of the functions on the website, then in this thesis an user-friendly E-Commerce website for LUGZ Shoes Collezione is made.This website is made by using HTML and PHP programming language for the pages, AJAX and Javascript for the functions, and MySQL for the database. The features which are developed in this website include: a login system for the access rights, the tracking system to track the status of the purchased goods and payment systems to conduct online transactions.The result of making this website is customers can easily see the products sold and make purchases of products on the website at the same time then make the payment confirmation online. Administrators can also perform Tracking order, so there is interaction between the store and online shoppers.